Comparison of clinical profile of urban vs. rural Indian youth with premature coronary artery disease (PCAD): a sub-study of the PCAD registry - Patil, Rahul; R., Raghu T.; N., Manjunath C.; Vijan, Vikrant; Ghosh, Santu (International Journal of Research in Medical Sciences, 2019)
Background: We aimed to compare clinical profile of premature coronary artery disease (PCAD) in urban vs. rural Indian populations. Methods: This was a prospective cross-sectional observational multi-centre study. This study is a sub-study of the ongoing PCAD registry. Between the period April 2017 and April 2018, a total of 1061 patients <40 years with PCAD were studied. Urban (n=583) and rural (n=478) populations were statistically compared. Results: Mean age of the urban and rural populations were 34.50±4.15 years and 33.99±4.46 years, respectively. All cardiovascular risk factors (smoking, diabetes, hypertension, dyslipidemia, obesity, diet and family history), except for alcoholism were more prevalent in urban subjects compared to rural subjects. However, higher prevalence of only hypertension (p=0.05) was statistically significant. Religion was significant between the two populations (p<0.001). Window period was also significant between the two populations (p<0.001). Very low density lipoprotein cholesterol (VLDL) (p=0.037) was significantly different between both populations. Conclusions: All conventional risk factors were more prevalent among urban populations than rural populations, however none of these differences except for hypertension was statistically significant.